Bridging Cultural Gaps: An Analysis of Cross-Cultural Communication Competence at the University of Halabja - Ali, Hemn Mohammed; Nathir Ghafar, zanyar; Amin, Avin; Jabbar, Solin; Kamal, Helin (Journal of Education and Learning Environments, 2026)
This study explores cross-cultural communication competence (CCC) at the University of Halabja in the Kurdistan Region of Iraq, where increasing cultural and linguistic diversity has created both valuable learning opportunities and notable communication challenges in academic settings. As higher education institutions in the region become more internationally and regionally diverse, understanding students' and lecturers' intercultural readiness has become essential. The study adopts a descriptive survey design and employs an online questionnaire adapted from Chen and Starosta's Intercultural Sensitivity Scale and Matveev and Nelson's CCC model. The questionnaire was distributed to 100 students and lecturers from various academic backgrounds who were conveniently selected. Frequency analysis revealed that most participants recognize the influence of culture on communication, demonstrate respect toward individuals from diverse backgrounds, and report patience in unfamiliar intercultural interactions, indicating relatively strong cognitive awareness and affective orientation. However, a high proportion of neutral responses regarding cooperation, flexibility, and willingness to engage in culturally challenging situations suggests uncertainty when participants face complex or unfamiliar intercultural tasks. Qualitative responses further highlighted respect, active listening, and adaptability as essential intercultural skills, although many respondents reported limited direct experience with intercultural conflict. Overall, the findings indicate a moderate level of cross-cultural communication competence: awareness and attitudes are evident, but behavioral confidence remains inconsistent. These baseline findings contribute to the limited empirical literature on CCC in Kurdish higher education and inform practical recommendations, including the integration of intercultural modules into curricula, the promotion of mixed-culture learning activities, and the implementation of scenario-based training to translate positive attitudes into effective communicative behavior.